Between Sepharad and Jerusalem : history, identity and memory of the Sephardim - Meyuhas Ginio, Alisa, 1937- (The Iberian Religious World, 2014)
Sephardim are the descendants of the Jews expelled from the lands of the Iberian Peninsula in the years 1492-1498, who settled down in the Mediterranean basin. The identifying sign of the Sephardim has been, until the middle of the twentieth century, the language known as Jewish-Spanish. The history, identity and memory of the Sephardim in their Mediterranean dispersal are analysed by the author with a special reference to the Sephardi community of Jerusalem and to the cultural and social changes that characterized the late nineteenth century and the first half of the twentieth century. However, because of the crucial changes related to modernization and the political circumstances that came into being at the turn of the nineteenth century and the first half of the twentieth century, the Sephardim lost their unique identity.